PENGARUH PELATIHAN, LINGKUNGAN KERJA DAN LOYALITAS KARYAWAN TERHADAP KINERJA KARYAWAN PADA PT HOTEL INSTAR KOTA BATAM - kelvin, kelvin; Nainggolan, Nora Pitri (SCIENTIA JOURNAL, 2021)
Every company or organization carries out various activities to achieve predetermined goals for profit, to achieve the goals of the company or organization must have a prominent advantage in order to compete with other companies, to be able to provide a prominent advantage, of course, must be supported by employee performance. The formation of employee performance in a company or organization cannot be separated from training, work environment and employee loyalty. Performance is the result of a job that employees provide to a company or organization. To improve employee performance is strongly influenced by training, work environment, and employee loyalty. The purpose of this study was to determine the effect of training, work environment, and employee loyalty on employee performance at PT Instar Hotel Batam City. The research method is causality which aims to determine the causal relationship between variables. Population of 107 employees. The data that has been collected will be processed using the SPSS version 25 application. The results show that training, work environment, and employee loyalty simultaneously have a significant influence on employee performance variables.